A mélange contribution to arc magmas recorded by Nd–Hf isotopic decoupling: An example from the southern Qiangtang Block, central Tibet. (November 2021) - Sun, Peng; Wang, Qiang; Hao, Lu-Lu; Dan, Wei; Ou, Quan; Jiang, Zi-Qi; Tang, Gong-Jian
Graphical abstract: Highlights: The Nd and Hf isotopes are decoupled in the Early Cretaceous rocks of SQB. Partial melting of subduction mélange induced the Nd-Hf isotopic decoupling. Mélange is an important medium for chemical exchange between crust and mantle. Abstract: Subduction zones are the main sites of material exchange between the crust and mantle. Sediments subducted at these zones are widely considered to play a key role in generating arc magmas. Here we report whole-rock Nd–Hf isotopic compositions of late Mesozoic intermediate–felsic igneous rocks from the southern Qiangtang Block, central Tibet. The late Jurassic Rena Co ( ca. 150 Ma) and Jiacuo ( ca. 152 Ma) granodiorites, which were derived from ancient lower crust, show Nd–Hf isotopic coupling (ΔεHf ( t ) = 0.7–2.4). Conversely, the early Cretaceous Rena Co granodiorite porphyries ( ca. 112 Ma), which were derived from juvenile lower crust, display marked Nd–Hf isotopic decoupling (ΔεHf ( t ) = 7.5). We suggest that the juvenile crust was compositionally andesitic and similar to the Duolong andesitic rocks (118–106 Ma) of the southern Qiangtang Block, which were derived by partial melting of the mélange (a physical mixture of mid-ocean ridge basalts, subducted sediments, and mantle-wedge peridotites). A simple mixing modeling indicates that the source of the early Cretaceous Duolong andesitic rocks includes 1–2% bulk subducted sediments. The Duolong andesitic rocks also show Nd–Hf isotopic decoupling (ΔεHf ( t ) = 3.0–11.3). Furthermore, the early Cretaceous Duolong dioritic and granitic rocks, which were generated by mixing between andesitic melts and ancient-lower-crust-derived magmas, display Nd–Hf isotopic decoupling. Thus, we infer a significant contribution of mélange melting in the Nd–Hf isotopic decoupling of early Cretaceous igneous rocks of the southern Qiangtang Block.